Continuance intention of autonomous buses: An empirical analysis based on passenger experience. (September 2022) - Yan, Yingying; Zhong, Shiquan; Tian, Junfang; Li, Tong
Abstract: The aim of this study was to understand passengers' continuance use intention with respect to autonomous buses (ABs) based on actual riding experience. Therefore, an extended technology acceptance model taking characteristics of both autonomous driving and buses into account was proposed, and 576 passengers with ABs riding experience in China responded to the survey. Several findings were revealed. First, characteristics of buses (including perceived in-vehicle safety, service quality and general attitudes toward buses) had positive effects on continuance use intention. Second, perceived road safety was not directly associated with continuance intention but had positive effects on perceived usefulness. Third, two significant moderating variables were revealed, namely, past bus riding habits and driver reliance (i.e., the degree to which passengers considered it important for ABs to have a driver). These observations suggest practical implications for policymakers and automakers. Highlights: This paper explored the continuous use intention of autonomous buses in China. ; A model considering the autonomous buses' riding experience was proposed. ; Two moderator variables (past bus riding habits and driver reliance) were verified. ; Perceived road safety and in-vehicle safety had different effects. ; Perceived enjoyment had effects on continuance intention to use autonomous buses.